2018
DOI: 10.3390/vetsci5040094
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Molluscicides and Schistosomiasis: What We Know and What We Still Need to Learn

Abstract: Worldwide schistosomiasis remains a serious public health problem with approximately 67 million people infected and 200 million at risk of infection from inhabiting or transiting endemically active regions. Africa, South America, the Caribbean, and the Middle East are the main transmission regions of Schistosoma mansoni. The fight against transmission through the use of molluscicides is not recent and has been advocated as the only activity with the possibility of interruption of transmission in small, epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Schistosomiasis remains a serious public health problem around the world particularly in Africa, South America, the Middle East, and the Caribbean. The use of molluscicides to control transmission is not recent (Augusto and Mello-Silva 2018). Recently, there has been an increased focus on immunostimulants to improve the host defense response and increase resistance to various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis remains a serious public health problem around the world particularly in Africa, South America, the Middle East, and the Caribbean. The use of molluscicides to control transmission is not recent (Augusto and Mello-Silva 2018). Recently, there has been an increased focus on immunostimulants to improve the host defense response and increase resistance to various diseases.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, although other possible active compounds might be present in the extract, we could link the cercaricidal activity of P. tithymaloides to the annotated diterpenoids 1 and 2. It has also been reported that the efficacy of Origanum compactum against S. haematobium cercariae was attributed to its terpenoids [51]. Most recently, Mohammed et al [48] have assigned the anthelmintic activity of the aqueous extract of Caralluma dalzielli against the cercariae stage of S. mansoni to his high terpenoids content.…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera Lamarck (Family: Moringaceae) is widely distributed in tropical and subtropical regions (Okonkwo et al, 2014). The extract of M. oleifera seeds contained bioactive molecules including saponins, lectins, (Ibrahim and Abdalla, 2017) which were known by its molluscicidal activity (Augusto and de Mello-Silva, 2018). Francis et al (2002) reported that the molluscicidal activity of saponins is due to their characteristic detergent effect on epithelial tissues of the snails and that of Flavonoids may act by inhibiting the detoxification system of the snail (de Souza et al, 2014).…”
Section: Discussionmentioning
confidence: 99%